APPLICATION PROGRAM SEARCH DATA IN VEHICLE DATA TENANTS AND PT. YANTO RENTCAR MOTOR USING VISUALBASIC 6.0 - Akhwan Khairul Alam; Ire Puspa Wardhani, SKom, MM (Jurnal Sistem Informasi, 2004)
Writing about the application view contains information about tenant data and vehicle data in PT. MOTOR YANTO RENTCAR, then it is expected that these applications can provide information quickly, efficiently, and accurately and reliably useful for both employees and the tenants themselves.In this information display applications the author uses visual basic program. Visual Basic is a software that not only limited to building database-based applications, but also can be used for a variety of other needs.With the information display application data in PT. MOTOR RENTCAR YANTO is expected in the data-data searches will be easier and faster in the presentation.